The Metafunction Meaning of Systemic Halliday to Analyze the Interpersonal Meaning in the Adele Album - Prahita Isnaini Ningtyas; Dwi Rukmini; Hendrikus Joko Yulianto (English Education Journal, 2023)
Music is a pattern of sounds made by musical instruments, voices, or computers, or a combination of these, intended to give pleasure to people listening to it. Interpersonal meaning, the strand of meaning that is the focus of this study, deals with how language is used in an interaction including in maintaining social relations, expressing attitudes and influencing others. In this study, the writers analized interpersonal meaning and using descriptive qualitative research. The writers searched the song of “21” album by Adele and only focus on Some One Like You song. The writers analyzed the clauses of the song based on that there are five types of deixis: spatial, temporal, person, social and discourse. After the researcher tries to interpret and interpret the lyrics, it can be concluded that the song Someone Like You tells about Adele's sick feelings, seeing her beautiful ex marry another woman, and having a happy life with her. Even though Adele still loves her ex-boyfriend very much and still can't forget his ex-girlfriend. Someone Like You is an amazing song. From the verses the lyrics teach the things that are really important. The following are some of the moral messages contained in Adele's Someone Like You lyrics is Learn to let go and Don't regret what happened.